2019
DOI: 10.1029/2019gc008477
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Multipulse Emplacement of a Postresurgent Pluton: The Case of Platoro Caldera Complex (Southern Rocky Mountain Volcanic Field, Colorado)

Abstract: Many eroded calderas expose associated postcollapse plutons, but detailed fieldwork‐supported studies have rarely focused on the internal structure that can contribute to understanding of emplacement dynamics. The Alamosa River monzonite pluton is a postcollapse intrusion at the Platoro caldera complex that erupted six large ignimbrites between 30.2 and 28.8 Ma in the Southern Rocky Mountains volcanic field. Magnetic fabrics in this intrusion indicate the pulsed emplacement of a vertically extensive pluton. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 142 publications
(259 reference statements)
1
8
0
Order By: Relevance
“…To improve volcanic hazard assessment, it is critical to understand how sub-volcanic plumbing systems are constructed and how their architecture controls eruption location and any intrusion-induced surface deformation patterns (e.g., Castro et al 2016; 2017; Cruden and Weinberg 2018). Our work supports previous studies from igneous intrusions of variable compositions by showing: (i) laccolith (and sill) construction may be incremental, and that the entire intrusion may be compartmentalized into constituent lobes between which magma mixing is limited, potentially meaning the volume of magma monogenetic eruptions could tap may be restricted (e.g., Thomson and Hutton 2004;Schofield et al 2012Schofield et al , 2017Galland et al 2019;Tomek et al 2019); (ii) evacuation of magma along inclined sheets emanating from the lateral terminations of a laccolith may feed eruptions laterally offset from the main area of forced folding and surface deformation, which will be centred above the inflating laccolith (e.g., Thomson 2007;Jackson 2012;Galland et al 2018;Schmiedel et al 2019); and (iii) pre-existing faults can provide important ascent pathways for magma, potentially controlling eruption location (e.g., Valentine and Krogh, 2006;Gaffney et al 2007;Bédard et al 2012;Holford et al 2012;Magee et al 2013a, b); (Mark et al 2019). Our study further emphasizes the importance to characterise the structural framework of active volcanic settings to monitor subsurface magma movement and location eruption.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To improve volcanic hazard assessment, it is critical to understand how sub-volcanic plumbing systems are constructed and how their architecture controls eruption location and any intrusion-induced surface deformation patterns (e.g., Castro et al 2016; 2017; Cruden and Weinberg 2018). Our work supports previous studies from igneous intrusions of variable compositions by showing: (i) laccolith (and sill) construction may be incremental, and that the entire intrusion may be compartmentalized into constituent lobes between which magma mixing is limited, potentially meaning the volume of magma monogenetic eruptions could tap may be restricted (e.g., Thomson and Hutton 2004;Schofield et al 2012Schofield et al , 2017Galland et al 2019;Tomek et al 2019); (ii) evacuation of magma along inclined sheets emanating from the lateral terminations of a laccolith may feed eruptions laterally offset from the main area of forced folding and surface deformation, which will be centred above the inflating laccolith (e.g., Thomson 2007;Jackson 2012;Galland et al 2018;Schmiedel et al 2019); and (iii) pre-existing faults can provide important ascent pathways for magma, potentially controlling eruption location (e.g., Valentine and Krogh, 2006;Gaffney et al 2007;Bédard et al 2012;Holford et al 2012;Magee et al 2013a, b); (Mark et al 2019). Our study further emphasizes the importance to characterise the structural framework of active volcanic settings to monitor subsurface magma movement and location eruption.…”
Section: Discussionsupporting
confidence: 88%
“…Some of the variations in fabric orientations within the broadly defined lobes could relate to possible smaller scale subdivisions into subsidiary flow units (e.g., magma fingers; Thomson and Hutton 2004). The persevered lobe boundaries as evidenced by the steeply dipping magnetic foliation zones were not overprinted during lobe coalescence, suggesting little mixing occurred between the lobes and an internal boundary was maintained (e.g., Magee et al 2012b;Tomek et al 2019). Such preservation of emplacement-related fabrics and a lack of mixing between the inferred lobes may occur because each magma pulse had a different rheology, perhaps reflecting incremental intrusion and the cooling of one pulse before the other was injected (e.g., Magee et al 2013aMagee et al , 2016Hoyer and Watkeys 2017).…”
Section: Laccolith Constructionmentioning
confidence: 99%
“…Lipman (1975) suggested that the Alamosa River pluton is the intrusive core of the volcano that sourced the compositionally similar Summitville Andesite. Magnetic fabrics in this intrusion suggest pulsed magma emplacement of a vertically extensive pluton (Tomek et al, 2019).…”
Section: Alamosa River Monzonitementioning
confidence: 91%
“…Accessory minerals include Fe-Ti oxides, titanite, apatite, and zircon. Lipman (1974Lipman ( , 1975 previously considered this intrusion to be a porphyritic phase of the Alamosa River pluton, but crosscutting contacts between the Alum Creek porphyry and Alamosa River monzonite are sharp, and the Alum Creek porphyry contains inclusions of equigranular Alamosa River monzonite (Calkin, 1967(Calkin, , 1971Tomek et al, 2019).…”
Section: Alum Creek Porphyrymentioning
confidence: 99%
See 1 more Smart Citation